Resilient Biophysical Phenotype of Memory CD4+ T Cells in Long-Lived Mice - Abarca-Ortega, A; Brito-Jara, E (WILEY, 2026)
Age-related alterations in the immune system-collectively known as immunosenescence-include both quantitative and qualitative changes across various immune cell populations, including B cells, natural killer cells and T lymphocytes, affecting their structure, phenotype and function. While these changes have been characterised biochemically and physiologically, their biophysical manifestations remain less understood, particularly in individuals that achieve exceptional longevity. Here, we investigate the mechanical and structural properties of memory CD4(+) T cells from mice across three aging stages: old (72 +/- 4 weeks), very old (96 +/- 4 weeks) and long-lived (> 120 weeks). We conducted a cross-sectional analysis combining micropipette aspiration, 3D confocal microscopy, spontaneous migration assays and flow cytometry to evaluate cellular stiffness, motility, nuclear morphology and cytoskeletal organisation. Our results confirm previous reports of increased stiffness and reduced migration in T cells from very old mice. However, this trend does not persist in long-lived individuals, who display mechanical and migratory properties similar to younger cohorts. Relative nuclear size (R-n/R-c) and actin organisation also stabilise in this group, suggesting the maintenance of intracellular architecture despite advanced chronological age. Notably, no significant changes were found in the expression levels or distribution of key structural proteins (actin, myosin, vimentin), nor in markers of DNA methylation (5-mC) or cellular senescence (p16). These findings support the concept of mechanical resilience in the immune system as a feature of successful aging, highlighting that certain biophysical traits may be preserved or selectively maintained in extreme longevity. This study provides novel evidence linking T cell mechanics with immune health and longevity and identifies candidate parameters for future investigations into aging biomarkers.